2001
DOI: 10.1038/sj.ejcn.1601152
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of retinol, tocopherol and carotenoid in Nepali pregnant and postpartum women following long-term β-carotene and vitamin A supplementation

Abstract: Objective: To characterize circulating carotenoid and tocopherol levels in Nepali women during pregnancy and post-partum and to determine the effects of b-carotene and vitamin A supplementation on their concentration in serum. Design: Randomized community supplementation trial. Setting: The study was carried out from 1994 to 1997 in the Southern, rural plains District of Sarlahi, Nepal. Subjects: A total of 1431 married women had an ascertained pregnancy, of whom 1186 (83%) provided an analyzable serum sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
1
21
0
2
Order By: Relevance
“…Women were asked to recall the number of times they had consumed 38 different types of vitamin A-and carotenoid-rich foods from a list that was developed using formative research on commonly consumed sources of vitamin A and b-carotene in this area of Nepal. Previously, we have shown that vitamin A and b-carotene food intakes, using the 7-day food frequency recall, were significantly associated with functional and biochemical indicators of vitamin A status such as maternal night blindness (Christian et al, 1998b) and low serum retinol (West et al, 1999) and carotenoid concentrations (Yamini et al, 2001). Mid-upper-arm circumference (MUAC), as a measure of nutritional status, was measured at both times.…”
Section: Methodsmentioning
confidence: 99%
“…Women were asked to recall the number of times they had consumed 38 different types of vitamin A-and carotenoid-rich foods from a list that was developed using formative research on commonly consumed sources of vitamin A and b-carotene in this area of Nepal. Previously, we have shown that vitamin A and b-carotene food intakes, using the 7-day food frequency recall, were significantly associated with functional and biochemical indicators of vitamin A status such as maternal night blindness (Christian et al, 1998b) and low serum retinol (West et al, 1999) and carotenoid concentrations (Yamini et al, 2001). Mid-upper-arm circumference (MUAC), as a measure of nutritional status, was measured at both times.…”
Section: Methodsmentioning
confidence: 99%
“…Anaemia was defined by Hb concentration as: mild, ,110 g/l or ,105 g/l for gestational age ,12 weeks or $12 weeks, respectively (20) ; moderate, ,90 to 70 g/l; and severe, ,70 g/l. Micronutrient deficiency was defined with the following cut-offs: Fe deficiency, ferritin ,12 mg/l or TfR .8?5 mg/l; retinol, ,0?70 mmol/l (18) ; a-tocopherol, ,9?3 mmol/l (21) ; vitamin B 12 , ,150 pmol/l (22) ; folate, ,6?7 nmol/l (23) ; and Zn, ,8?6 mmol/l (24) . An additional less conservative cut-off of ,12 mmol/l was also used to define a-tocopherol deficiency (25) .…”
Section: Discussionmentioning
confidence: 99%
“…These assays were performed at the Johns Hopkins University Center for Human Nutrition on a representative subset of all the available samples, while retinol and tocopherols were assessed on all samples. Retinol, a-tocopherol and g-tocopherol were determined simultaneously by reverse-phase HPLC at Mahidol University in Thailand using the method of Yamini et al (18) . The within-and between-assay CV for plasma samples were ,10 % for all analytes except a-and g-tocopherol, for which inter-assay CV were , 20 %.…”
Section: Methodsmentioning
confidence: 99%
“…Peaks were detected with a photodiode array detector (Waters 2996; Waters Corporation) at 325 and 295 nm for retinol and tocopherols, respectively. 39 Peak area was calculated using Empower software (Waters Corporation). Deficiency was defined as circulating retinal less than 0.7 μmol/L and α-tocopherol less than 12 μmol/L.…”
Section: Methodsmentioning
confidence: 99%